The Assessment of the Biocompatibility of Dental Alloys and Alloys for Dental Amalgam. Part First - Z. Broukal; V. Fialová; J. Novotný (Czech Dental Chamber, 2014)
Background: Dental alloys are widely used in applications where they come for a long time into contact with oral epithelium, connective tissue or alveolar bone. Hence their biocompatibility is one of the critical requirements for use in clinical dentistry. This review of literature is intended as an overview of the risk exposure of the human body to metals from dental alloys and the possibility of examining the model conditions in vitro and in vivo before placing them on the market and put into use. Dental alloys are metallurgically complex ones and with regard to their composition. They are divided into gold, silver and palladium based alloys and non-precious alloys (cobalt, chromium, nickel). Crucial features of alloys in terms of their biocompatibility are their corrosion properties. The individual components of alloys released into the oral environment and the organism due to the in situ corrosion processes can cause local and systemic toxicity, and therefore it is necessary the alloys in the preclinical stage to properly investigate. Attention is focused especially on local toxicity, since systemic toxicity from dental alloys has not been demonstrated. Standard contact cytotoxicity tests whether performed in vitro in cell cultures or in vivo in laboratory animals simulate the situation in the clinical use only partially, and therefore it is necessary to take into consideration the general toxicological properties of the individual metals in dental alloys. Conclusion: In the first part of the literature review of the dental alloys biocompatibility and its testing the data gained from the last fifteen to twenty years are summarized.